Toxoplasma Hypervirulence in the Rat Model Parallels Human Infection and Is Modulated by the Toxo1 Locus - Corinne Loeuillet; Anais Mondon; Salima Kamche; Véronique Curri; Jean Boutonnat; Jean Boutonnat; Pierre Cavaillès; Marie-France Cesbron-Delauw (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasmosis is considered as an opportunistic parasitic disease. If post-natally acquired in children or adults, it may pass unnoticed, at least with strains of European origin. However, in the wild biotopes especially in South America, Toxoplasma gondii strains display a greater genetic diversity, which correlates to higher virulence for humans, particularly along the Amazon River and its tributaries. In French Guiana, several atypical strains have been associated with severe clinical forms: ocular toxoplasmosis and acute respiratory distress syndrome both of which can result in death. Among these, the GUY008-ABE strain was responsible for an epidemic of severe disseminated toxoplasmosis in Suriname, which led to the death of one immunocompetent individual. To better understand the mechanism underlying the hypervirulence of the GUY008-ABE strain, we have tested the rat model which compared to the mouse, better reflects the immune resistance of humans to Toxoplasma infection. Here we compare the outcome of toxoplasmosis in F344 rats infected either by the GUY008-ABE strain or the type II Prugniaud strain. We show that the GUY008-ABE strain displays a higher virulence phenotype leading to the death of all infected rats observed in this study. GUY008-ABE infection was characterized by an increase of the parasite load in several organs, especially the heart and lung, and was mainly associated with severe histological changes in lungs. Moreover, correlating with its hypervirulence trait, the GUY008-ABE strain was able to form cysts in the LEW rat model otherwise known to be refractory to infection by other Toxoplasma strains. Together, these results show that the rat is a discriminating experimental model to study Toxoplasma virulence factors relevant to the pathogenesis of human infection and that the degree of virulence is linked to the Toxo1 locus.